Examples of How to Find the Derivative Using The Power Rule and Product Rule

# Examples of How to Find the Derivative Using The Power Rule and Product Rule

This preview shows pages 1–3. Sign up to view the full content.

Examples of How to Find the Derivative Using The Power Rule, Product Rule, Quotient Rule and Chain Rule Power Rule Examples: 1. y = 3x 4 -2x + 1 y’ = 12x 3 -2 2. y = 3 x y = x 3 1 y’ = 3 2 3 1 - x 3. y = 12x 5 + 3x 4 -5x y’ = 60x 4 + 12x 3 -5 4. y = x + x 1 y = 2 1 2 1 - + x x y’ = 2 3 2 1 2 1 2 1 - - - + x x 5. v(r) = π 3 4 r 3 v’(r) = 4 r 2 6. f(x) = 12 f’(x) = 0 7. f(x) = 3x 4 (x 2 -2x + 1) f(x) = 3x 6 -6x 5 +3x 4 f’(x) = 18x 5 -30x 4 +12x 3 8. f(t) = 4 4 4 4 1 t t - f’(t) = t t 4 5 3 1 1 - +

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Product Rule Examples: 9. f(x) = 4x(3x 2 + x ) f’(x) = 4x (6x + 2 1 2 1 - x ) + 4 (3x 2 + x ) 10. y = (2x 2 + 5) (4x – 1 ) y’ = (2x 2 + 5) (4) + (4x) (4x – 1 ) 11. t(x) = (2x 4 – 1)(5x 3 + 6x) t’(x) = (2x 4 – 1)(15x 2 + 6) + (8x 3 ) (5x 3 + 6x) 12. y = ) 3 )( 1 ( 3 x x x + y = ) 3 )( ( 2 1 2 1 3 1 x x x - + y’ = ) 3 )( 2 1 3 1 ( ) 2 3 )( 1 ( 2 3 3 2 2 1 3 x x x x x x - - - - + + 13. f(x) = (4x 2 )(3x + 5)(6x 2 + x) f”(x) = (4x 2 )[ (3x + 5)(12x + 1) + (3)( 6x 2 + x)] + 8x (3x + 5)(6x
This is the end of the preview. Sign up to access the rest of the document.

## This note was uploaded on 10/09/2011 for the course ASTRO 47280 taught by Professor Islam during the Spring '09 term at Ball State.

### Page1 / 3

Examples of How to Find the Derivative Using The Power Rule and Product Rule

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online